Analysis of the Influence of Tourism Growth on Economic Growth and Human Development Index in West Java Province 2012-2018 - Muhammad Andi Auliya Hakim; Agustinus Suryantoro; Mugi Rahardjo (Budapest International Research and Critics University, 2021)
This study aims to determine how the influence of tourism growth as measured by the number of tourists to tourism objects, the number of tourists to accommodation, the number of hotels and accommodation, and the number of restaurants and restaurants on economic growth as measured by GRDP and Human Development Index in West Java Province. 2012-2018. The population that becomes the object of this research is the regency / city in West Java Province. The data used in this study is secondary data taken from the Central Statistics Agency (BPS) and the West Java Provincial Tourism Office. In this study using path analysis. Based on the analysis that has been carried out in this study, the results show that the variable number of tourists to accommodation and the number of restaurants and restaurants has a positive and significant effect on GRDP, while the variable number of tourists to tourism objects and the number of hotels and accommodation is not significant to the GRDP in Java Province. West. GRDP has a significant positive effect on the Human Development Index in West Java Province. The number of tourists to accommodation is the variable that has the greatest indirect effect on the Human Development Index.